Early Outcomes in the ROADSTER 2 Study of Transcarotid Artery Revascularization in Patients With Significant Carotid Artery Disease. Issue 9 (September 2020) - Kashyap, Vikram S.; Schneider, Peter A.; Foteh, Mazin; Motaganahalli, Raghu; Shah, Rasesh; Eckstein, Hans-Henning; Henao, Steve; LaMuraglia, Glenn; Stoner, Michael C.; Melton, Jim; Massop, Douglas; Hanover, Tod; et al.
Abstract : Background and Purpose: Transcarotid artery revascularization (TCAR) is comprised of carotid artery stent placement with cerebral protection via proximal carotid artery clamping and reversal of cerebral arterial flow. The aim of the present study was to evaluate the safety and efficacy of TCAR performed by a broad group of physicians with variable TCAR experience. Methods: The ROADSTER 2 study is a prospective, open label, single arm, multicenter, postapproval registry for patients undergoing TCAR. Patients considered at high risk for complications from carotid endarterectomy with symptomatic stenosis ≥50% or asymptomatic stenosis ≥80% were included. The primary end point was procedural success, which encompassed technical success plus the absence of stroke, myocardial infarction, or death within the 30-day postoperative period. Secondary end points included technical success and individual/composite rates of stroke, death, and myocardial infarction (MI). All patients underwent independent neurological assessments before the procedure, within 24 hours, and at 30 days after TCAR. An independent clinical events committee adjudicated all major adverse events. Results: Between 2015 and 2019, 692 patients (Intent to Treat Population) were enrolled at 43 sites. Sixty cases had major protocol violations, leaving 632 patients adhering to the Food and Drug Administration-approved protocol (per-protocol population). The majority (81.2%) of operators were TCAR naïve before study initiation. Patients underwent TCAR for neurological symptoms in 26% of cases, and all patients had high-risk factors for carotid endarterectomy (anatomic-related 44%; physiological 32%; both 24%). Technical success occurred in 99.7% of all cases. The primary end point of procedural success rate in the Intent to Treat population was 96.5% (per-protocol 97.9%). The early postoperative outcomes in the Intent to Treat population included stroke in 13 patients (1.9%), death in 3 patients (0.4%), and MI in 6 patients (0.9%). The composite 30-day stroke/death rate was 2.3%, and stroke/death/MI rate was 3.2%. In the per-protocol population, there were strokes in 4 patients (0.6%), death in one patient (0.2%), and MI in 6 patients (0.9%) leading to a composite 30-day stroke/death rate of 0.8% and stroke/death/MI rate of 1.7%. Conclusions: TCAR results in excellent early outcomes with high technical success combined with low rates of postprocedure stroke and death. These results were achieved by a majority of operators new to this technology at the start of the trial. Adherence to the study protocol and peri-procedural antiplatelet therapy optimizes outcomes. Longer-term follow-up data are needed to confirm these early outcomes. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02536378.